Level of Proficiency in Arabic and English, and Identity of Emirati Students in UAE Public Schools - Masri, Taghreed Ibrahim (2012)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Taghreed Ibrahim Masri entitled, "Level of Proficiency in Arabic and English, and Identity of Emirati Students in UAE Public Schools," May 2012. Thesis advisor is Dr. Fatima Badry. Available are both hard and soft copies of the thesis.